2021
DOI: 10.1177/25160435211008347
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of patients’ safety culture practices in a tertiary hospital in Nigeria

Abstract: Background There is growing concern towards ensuring that patients are safe. Despite this, factors influencing safety practices and outcomes in healthcare delivery systems in Nigeria have not been determined exhaustively. Objective To determine the factors affecting patient safety culture (PSC) practices in a tertiary hospital in Nigeria. Materials and methods This cross-sectional descriptive study of care providers in a tertiary hospital in Nigeria was conducted from June to November, 2016. A self-administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…The study revealed that healthcare professionals in those hospitals had average patient safety culture and that there are some areas that require urgent attention for improvement. The overall level of patient safety culture of this study is comparable to findings from Nigeria, China, Taiwan, and Iran [19][20][21][22][23] .…”
Section: Discussionsupporting
confidence: 80%
“…The study revealed that healthcare professionals in those hospitals had average patient safety culture and that there are some areas that require urgent attention for improvement. The overall level of patient safety culture of this study is comparable to findings from Nigeria, China, Taiwan, and Iran [19][20][21][22][23] .…”
Section: Discussionsupporting
confidence: 80%